Compulsivity Across the Pathological Misuse of Drug and Non-Drug Rewards - Banca, Paula; Harrison, Neil A.; Voon, Valerie (Frontiers in Behavioral Neuroscience, 2016)
Behavioral adaptation is required for the successful navigation of a constantly changing environment. Impairments in behavioral flexibility are commonly observed in psychiatric disorders including those of addiction. This study investigates two distinct facets of compulsivity, namely reversal learning and attentional set shifting, implicating orbitofrontal and lateral prefrontal regions respectively, across disorders of primary and secondary rewards. Obese subjects with and without binge eating disorder (BED), individuals with compulsive sexual behaviors (CSB), alcohol use disorder (AUD) and pathological video-gaming (VG) were tested with two computerized tasks: the Probabilistic Reversal Task (trials to criterion and win-stay/lose-shift errors) and the Intra/Extra-dimensional Set Shift Task (IED). Individuals with AUD and pathological video-gaming were slower at reversal learning irrespective of valence, with AUD subjects more likely to perseverate after losses. Compared to obese subjects without BED, BED subjects were worse at reversal learning to wins but better at losses highlighting valence effects as a function of binge eating. CSB subjects demonstrated enhanced sensitivity to reward outcomes with faster acquisition and greater perseveration with higher magnitude rewards. We further show an impairment in attentional set shifting in individuals with BED and AUD relative to healthy volunteers. This study provides evidence for commonalities and differences in two distinct dimensions of behavioral inflexibility across disorders of compulsivity. This study provides evidence for commonalities and differences in two distinct dimensions of behavioral inflexibility across disorders of compulsivity. We summarize studies on compulsivity subtypes within this same patient population. We emphasize commonalities in AUD and BED with impairments across a range of compulsivity indices, perhaps supporting pathological binge eating as a form of behavioral addiction. We further emphasize commonalities in reversal learning across disorders and the crucial role of valence effects. These findings highlight the role of behavioral inflexibility and compulsivity as a relevant domain in defining dimensional psychiatry and the identification of relevant cognitive endophenotypes as targets for therapeutic modulation.